Instructional Design For The Teaching Of Speaking At The First Semester Of English Department Of Muhammadiyah University Of Surakarta In Academic Year 2014/2015 - Sari, Novi Arum, Prof. Dr. Endang Fauziati, M. Hum, Nur Hidayat, M.Pd (2015)
The study is aimed at observing the instructional design for teaching speaking at Muammadiyah University of Surakarta. In this research, there are nine components of instructional design, namely: (1) learning objective. (2) syllabus. (3) roles of instructional material. (4) classroom procedure. (5) classroom technique (6) teacher's role. (7) learner's role. (8) media. (9) assessment model. The type of the study is descriptive qualitative. In this research, the data are derived from event, informant and field note. There are three techniques of collecting the data, namely: observation, interview and document. The techniques of analyzing data are data reduction, data display and verification/conclusion. The result of the study, such as: (1) There are two learning objective of teaching speaking namely: general objective and specific objective. General learning objective based on competence standart is taken from syllabus. Specific learning objective of teaching English is written in basic competence is taken from lesson plan. (2) The type of syllabus is Notional-functional syllabus. (3) The instructional material of speaking are based on the syllabus, printed material taken from speaking I student's copies book. The instructional material of speaking skill in Muhammadiyah University of Surakarta is simple and complex materials. (4) The classroom procedure used is 5E (Engangement, Exploration, Explanation, Elaboration, and Evaluation). (5) Teaching technique used in teaching English are some techniques in speaking such as brainstorming, story telling, discussion and roleplay. The lecturer uses the instructor feedback and peer-editing. (6) The teacher's role are as facilitator, as instructor, as classroom manager, as consultant and as evaluator. (7) The learner's role are as monitor and evaluate their own progress. The learners learn from the lecture and the learner the other student's presentation or performance. (8) The media used in teaching learning process are student's copy book as printed media, LCD projector and whiteboard. (9) The assessment model used are homework, mid test and final test.